Complications of Tonsillectomy, Adenoidectomy and Adenotonsillectomy in Chittagong Medical College Hospital (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
It is a prospective study is done with materials of 100 cases of Tonsillectomy patient giving Proper attention to age, sex, Indication of operation, Clinical Presentation, Duration of Operation, Post operative complications. Altogether 100 Patients of whom 54 were male and 46 female, collected for a period of 6 months from 16th July 2001 to 15th January 2002 with  maximum age group 48% were of 20+years and a sex ratio of Male: female 1.17:1 were included in the series the commonest indication is Recurrent tonsillitis was 83%. Among them clinical presentation, Patients presented with recurrent pain in throat (85%), History of Fever in 62% and difficulty in swallowing in 46%. Regarding duration of operation 40% Patients were operation within 30 to 39 minutes, 31% patients were operated within 40 to 49 minutes. In this Series, Complications that encountered after operation were hemorrhages both reactionary and secondary 1% and 2% respectively, operative local trauma in 4% cases and local infection in tonsillar bed in 6% cases. In this Series one patient needed second time general anaesthesia.DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i2.21047